Beyond the Courtroom Confidence: Investigating the Relationship Between Imposter Phenomenon and Grit in Legal Professionals - Sandhu, Nehchal; Kaur, Harprit (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This study examined the relationship between Imposter Phenomenon and Grit among legal professionals, focusing on gender differences in these psychological constructs. A sample of 50 legal professionals aged 25-40 years, practicing in Punjab and Haryana High Court, participated in the study. Using the Clance Impostor Phenomenon Scale and Short Grit Scale, data was analysed through t-tests and correlational analysis. Results revealed a significant negative correlation between Imposter Phenomenon and Grit. Gender differences were observed, with male legal professionals showing higher levels of Imposter Phenomenon (self-doubt), while female legal professionals demonstrated higher levels of both Grit and work-related stress. The findings contribute to understanding psychological resilience in the legal profession and highlight the complex interplay between self-doubt and perseverance in high-stakes professional environments.